Mutamorphosis: Tribute to Uncertainty - Horáková, Jana (Teorie vědy / Theory of Science, 2013)
Zpráva z konference / Conference Report Mutamorphosis: Tribute to Uncer- tainty. International Centre for Art and New Technologies (CIANT). Praha, 6.-8. prosince 2012.